STUDENTSâ€™ PERCEPTION TOWARD NAHW LEARNING AT STATE ISLAMIC COLLEGE (PTKIN) IN SUMATERA / Ø¥Ø¯Ø±Ø§Ùƒ Ø§Ù„Ø·Ù„Ø§Ø¨ Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù†ØÙˆ ÙÙŠ Ø§Ù„Ø¬Ø§Ù…Ø¹Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ø¨Ø¬Ø²ÙŠØ±Ø© Ø³ÙˆÙ…Ø·Ø±Ø© - Kamaluddin Kamaluddin (IAIN Batusangkar, Indonesia, 2022)
This study aims to determine students’ perception of learning Nahw (Arabic grammar) at Arabic Education Department at PTKIN in Sumatera. Survey method was used in this research. The population was the second and third year students of Arabic Education Department of UIN Mahmud Yunus Batusangkar, UIN Imam Bonjol Padang, and IAIN Curup, and the sample was 39 students. Data were collected using questionnaire and then analyzed using quantitative descriptive techniques. The results showed that 59% students stated that the objective of learning Nahw were very clear, and 53.8% students agreed that Nahw material met its objectives. Meanwhile, 35.9% students strongly agreed with the order of Nahw materials, 43.6% students strongly agreed with the learning method used by lecturers, 30.8% students stated that media were always used in Nahw learning, 30.8% students said that evaluation was given in oral and written form, and 56.41% students mentioned that the evaluation was done theoretically and practically. However, there were only 7.7% students said that learning Nahw was very easy, 10.4% students were familiar with the materials, and 2.56% agreed that understanding Nahw could assist them in comprehending other Arabic materials. Based on students’ perceptions, learning Nahw has not fully met their expectation in terms of material, method, media, and learning evaluation.